Data transfer analysis of the homogeneous rough surface of a solid model into a CAE system with varying file data formats. Issue 1 (31st December 2022) - Kartini, K.; Sipayung, G.A.; Ismail, R.; Jamari, J.; Bayuseno, A.P.
Abstract: Design and manufacturing process activities of a product require different software applications for facilitating to test of replicas without the need for a physical model. Practically, CAE (computer-aided engineering) software can be used for simulation analysis with FEM (finite element method) and other engineering programs. This study was undertaken to analyze the CAD (computer-aided design) file of a homogeneous rough surface model that can be integrated into CAE software (i.e. ABAQUS) with reduced file size. The rough surface of the static contact model for CAE software analysis was presented in different file formats, namely; solid part (*.sldprt), IGES (*. igs), STEP (*.stp), Parasolid part (*.x.t), and ACIS (*sat) files. The comparative analysis of each file for the static contact model was performed from CAD file, ODB (Open Document Database) file, and CAE file. The obtained file formats did not result in any difference in the geometry of the surface model. Among file formats present, using a typical Parasolid part file for simulations of static rough surfaces seemed to be superior by generating the smallest size files. The results of the study would add knowledge for enhancing CAD interoperability with the CAE program.